Behavior, Environment, and Administrative Services Based on Patients’ Perceptions: A Cross-Sectional Survey for Caring Behavior of Emergency’s Nurses in Indonesia - Suroso, Jebul; Yuliarti; Kuntoro (International Journal of Psychosocial Rehabilitation, 2020)
The application of caring in services in Hospital Emergency Departments (HED) is the key to patient satisfaction and safety. Caring services at hospitals ED in Indonesia include three integral aspects, namely the behavior of staffs, the environment, and administrative services. These three aspects of several hospitals in Indonesia are still not optimal, resulting in a lack of patient and family satisfaction. This study aims to describe the implementation of caring in aspects of behavior, environment, and administration in services in emergency departments in several hospitals in Indonesia. This type of survey research involved 480 respondents; emergency room patients who came from four hospitals in Indonesia, those are Medan, Jambi, Pontianak, and Gorontalo. The data collection used a caring scale instrument (GCS-46), while the data analysis was performed with descriptive analysis, and the results are presented in a frequency distribution table. The results showed the implementation of caring in the ED was generally perceived sufficiently by respondents with a score of 78.75, with a detailed score of behavior 79.53, an environmental score of 78.75, and an administrative score of 76.76. The conclusion obtained from this study is that the description of caring in the ED of several hospitals in Indonesia is generally perceived to be sufficient. So it is necessary to increase caring services in aspects of behavior, environment, and administration in the hospital emergency departments to reach a good level or even very good.